REVEAL risk score in patients with chronic thromboembolic pulmonary hypertension receiving riociguat - Benza, Raymond L.; Farber, Harrison W.; Frost, Adaani; Grünig, Ekkehard; Hoeper, Marius M.; Busse, Dennis; Meier, Christian; Nikkho, Sylvia; Ghofrani, Hossein-Ardeschir (The journal of heart and lung transplantation, 2018)
Background - The REVEAL risk score (RRS) was developed to predict survival in patients with pulmonary arterial hypertension (PAH), based on multiple patient characteristics. Herein we calculated RRS for patients in the randomized CHEST-1 study and open-label CHEST-2 extension study of riociguat in inoperable or persistent/recurrent chronic thromboembolic pulmonary hypertension (CTEPH). We investigated the effect of riociguat vs placebo on RRS in the CHEST-1 study, and the relationship between RRS and long-term outcomes in the CHEST-2 study. - Methods - RRS was calculated post hoc for baseline and Week 16 of CHEST-1 and Week 12 of CHEST-2, based on 9 evaluable elements. Patients were grouped into risk strata by RRS. Relationships between RRS and both survival and clinical worsening-free survival were examined by Kaplan-Meier and Cox proportional hazards analyses. - Results - Overall, 237 patients completed CHEST-1 and entered CHEST-2. In CHEST-1, riociguat significantly improved RRS (p < 0.0001) and risk stratum (p < 0.001) vs placebo from baseline to Week 16. RRS at baseline, and at Week 16, and change in RRS during CHEST-1 were significantly associated with survival (hazard ratios for a 1-point reduction in RRS: 0.702, 0.692, and 0.682, respectively) and clinical worsening-free survival (hazard ratios: 0.697, 0.719, and 0.754, respectively) over 2 years in CHEST-2. - Conclusions - Riociguat improved RRS in patients with inoperable and persistent/recurrent CTEPH. RRS at baseline and Week 16, and change in RRS from baseline, predicted survival and clinical worsening-free survival. This analysis of RRS in patients with inoperable or persistent/recurrent CTEPH suggests utility for the RRS in indications beyond PAH.
Gesehen am 25.02.02.2020